What are the impacts of devolution on agricultural civil servants and services in Ghana? - Resnick, Danielle (International Food Policy Research Institute, 2018)
In 2009, Ghana passed Local Government Instrument 1961 (LI 1961) to devolve a set of functions from the central government to the country’s 216 Metropolitan, Municipal, and District Assemblies (MMDA). Agriculture, along with public works and social welfare, was among the first sectors to be devolved. This transfer was formally institutionalized in 2012. In addition, LI 1961 stipulated that the staff of the MMDA departments were to be transferred from the national civil service to a newly created Local Government Services (LGS). A composite budget system also was introduced, which integrated the budgets of all departments of the MMDAs into the overall budget for the MMDA.